SYNTHESIS OF CHALCONES VIA CLAISEN–SCHMIDT CONDENSATION REACTION CATALYZED BY SILICA-H2SO4 UNDER ULTRASOUND IRRADIATION - Lahyani, Achraf; Chtourou, Manef; Frikha, Mohamed Hédi; Trabelsi, Mahmoud (JOURNAL OF ADVANCES IN CHEMISTRY, 2014)
The synthesis of 1,3-diaryl-2-propenones was carried out by using ultrasonic irradiation in the presence of silica-H2SO4, which was used as a catalyst in solvent-free conditions. The advantages of this process are the high yields (82–98%) it produces, the cost effectiveness of the catalyst, and the simple work-up and purification of products achieved via a non-chromatographic method.